2011
DOI: 10.1364/ol.36.001365
|View full text |Cite
|
Sign up to set email alerts
|

Multipulse gate-delayed range gating imaging lidar

Abstract: We present a technique to reconstruct a higher resolution of depth map of range gating imaging lidar by applying the delays of the gates to a typical range gating lidar system during the detection of each returned laser pulse with the encoding of the returned signal. With the consequent delays of the gate, the depth of the scene is extended accordingly. A multipulse gate-delayed range gating lidar system is designed to prove the resolution improvement from 6 to 1.5 m. The unchanged peak power of the laser, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[1][2][3][4] In this work we built a frequency doubled nanosecond pulsed Nd:YAG laser as illumination source, a CCD coupled to a generation II image intensifier and a simple progressive delays set for the camera gate using a pulse delay generator to show the potential of this technique as well as to further determine aspects such as the typical energy per pulse needed and the illumination distribution of the laser source. Surprisingly, at low levels of the illumination pulse energy that would satisfy the safety laser class 2, we can resolve objects as far as 690 m.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In this work we built a frequency doubled nanosecond pulsed Nd:YAG laser as illumination source, a CCD coupled to a generation II image intensifier and a simple progressive delays set for the camera gate using a pulse delay generator to show the potential of this technique as well as to further determine aspects such as the typical energy per pulse needed and the illumination distribution of the laser source. Surprisingly, at low levels of the illumination pulse energy that would satisfy the safety laser class 2, we can resolve objects as far as 690 m.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a 3D image can be reconstructed from multiple pulses by scanning the scene with a 1D laser fan beam [1,[12][13][14] . Range accuracy is one of the most critical features of imaging lidar systems [15][16][17] . Gleckler et al have reported that the achievable range error for an STIL system can be estimated by [5,7,8,18]…”
mentioning
confidence: 99%
“…To achieve the highest range accuracy, Zhang et al [6] proposed an optimal bin number. Wu et al [7] presented a multi-pulse gate-delayed method to improve the resolution of rangegating imaging lidar without changing the peak power and width of laser pulses.…”
mentioning
confidence: 99%
“…With the delayed gate, the system obtains 5 laser intensity images for the range bins of 475 to 500, 480 to 505, 485 to 510, 490 to 515, and 495 to 520. To acquire higher resolution, the system sets the delayed period of the gates as the length of the sub-range bin, thereby dividing the range bin into multiple sub-range bins of about 5 m. With the coded algorithm [7] , the range-gating delayed lidar system constructs a depth map (Fig. 4).…”
mentioning
confidence: 99%
See 1 more Smart Citation